Stability of Norwalk Virus Capsid Protein Interfaces Evaluated by in Silico Nanoindentation - Boyd, Kevin J.; Bansal, Prakhar; Feng, Jun; May, Eric R. (Frontiers in Bioengineering and Biotechnology, 2015)
Norwalk virus causes severe gastroenteritis for which there is currently no specific anti-viral therapy. A stage of the infection process is uncoating of the protein capsid to expose the viral genome and allow for viral replication. A mechanical characterization of the Norwalk virus may provide important information relating to the mechanism of uncoating. The mechanical strength of the Norwalk virus has previously been investigated using atomic force microscopy (AFM) nanoindentation experiments. Those experiments cannot resolve specific molecular interactions, and therefore we have employed a molecular modeling approach to gain insights into the potential uncoating mechanism of the Norwalk capsid. In this study, we perform simulated nanoindentation using a coarse-grained structure based model, which provides an estimate of the spring constant in good agreement with the experimentally determined value. We further analyze the fracture mechanisms and determine weak interfaces in the capsid structure which are potential sites to inhibit uncoating by stabilization of these weak interfaces. We conclude by identifying potential target sites at the junction of a weak protein-protein interface.